Keterampilan Guru Dalam Membuka Dan Menutup Pembelajaran DI SMA Negeri 1 OKU - Siti A.R Putri; Dona P Liverti; Asry Romadoni; Ning Antariningsih; Ervian Agus S; Yulita Yulita (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
The purpose of this study was to determine the teacher's skills in opening and closing learning at SMA Negeri 1 OKU. The type of research used is quantitative research Data collection techniques arewith questionnaires and data collection tools in the form of questionnaires. The population and sample in this study were all teachers at SMA Negeri 1 OKU, and for sampling, a total sampling of 48 people. Research data were analyzed using the percentage formula. The results of research regarding the teacher's ability to open learning as much as 99% said always and often with the criteria included in the very good category, while the teacher's ability to close learning as much as 99% stated always and often, thus it can be concluded that it was included in very good. Based on the results of the data obtained, it can be concluded that the teacher's ability to open and close learning at SMA Negeri 1 OKU can be said to have been carried out